2020
DOI: 10.3390/ijerph17145192
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Gender, Alcohol Use and Negative Consequences among Korean College Students: A National Study

Abstract: This study examines Korean college students’ rates and the severity of various negative consequences resulting from the frequency and quantity of alcohol consumption and the unique factors that are affecting this problem in the Korean context in comparison to other countries. It assesses how much gender, age and other associated respondent characteristics mediate alcohol use and the resulting negative consequences among the population. A stratified representative sample of 4803 valid student respondents attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
5
0
3
Order By: Relevance
“…The alcohol consumption (AC) among university students is different between countries, due to cultural differences, family socioeconomic status, level of education, socialactivity, health, and religious reasons [1][2][3]. Nowadays, students drink more than earlier generations, with increasing emphasis on binge drinking and drunkenness [4].…”
Section: Introductionmentioning
confidence: 99%
“…The alcohol consumption (AC) among university students is different between countries, due to cultural differences, family socioeconomic status, level of education, socialactivity, health, and religious reasons [1][2][3]. Nowadays, students drink more than earlier generations, with increasing emphasis on binge drinking and drunkenness [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that drinking norms play an important role in classifying masculinity as part of masculinity norms [ 11 ]. According to Chung et al (2012) and Allen Rose et al (2020), a close relationship exists between drinking norms and traditional gender role attitudes in Korea, leading to more drinking in men [ 38 , 39 ]. In particular, it is known that young men are greatly affected by drinking norms because young men, such as college students, have relatively more organized and explicit drinking norms than other population groups [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the decrease observed in recent years, these values continue to cause alarm, since teenagers are a particularly vulnerable group to the effects of alcohol and it is at these ages that poor health habits are usually initiated [ 7 ]. Alcohol consumption in adolescents is associated with significant negative biological and social effects, such as neurological affectation in the short and medium term with poor academic performance [ 8 ]; increased risk of sexually transmitted infections and unwanted pregnancies, and increased risk of physical and sexual aggression and other violent events [ 9 , 10 , 11 ]; increased consumption of other psychostimulant substances [ 12 ]; increased risk of chronic and long-term diseases such as cancer, cardiovascular diseases, etc. [ 13 ].…”
Section: Introductionmentioning
confidence: 99%